STRATEGI KOMUNIKASI VECHA EVENT DALAM MEMBANGUN BRAND AWARENESS MELALUI MEDIA SOSIAL INSTAGRAM - Khoerunnisa, Nur Syifa; Rici Tri Harpin Pranata (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT The development of social media has encouraged companies to implement effective digital communication strategies in building brand awareness. This study employed a qualitative approach with a descriptive method. Data were collected through active participation, observation, interviews, and literature review during an internship program at Vecha Event. The results indicate that Vecha Event implements digital communication strategies through structured content planning, consistent visual identity, and the utilization of Instagram’s interactive features such as Reels, polls, question boxes, hashtags, and call-to-action elements. Content pillar strategies such as Highlight, QnA with Bang Ipen, Seputar Event , and Riding The Wave were able to increase audience engagement and strengthen the company's brand character. The implementation of these strategies contributed to the growth of followers, likes, comments, and views on the Instagram account @vecha.event. This study demonstrates that Instagram plays an important role in establishing effective digital communication to enhance brand awareness in the event organizer industry. Keywords: digital communication strategy, social media, Instagram, brand awareness, event organizer. ABSTRAK Perkembangan media sosial mendorong perusahaan untuk menerapkan strategi komunikasi digital yang efektif dalam membangun brand awareness. Pendekatan kualitatif dengan metode deskriptif diterapkan dalam penelitian ini. Pengumpulan data dilakukan melalui partisipasi aktif, observasi, wawancara, dan studi literatur selama kegiatan Praktik Kerja Lapangan di Vecha Event. Hasil penelitian menunjukkan bahwa Vecha Event menerapkan strategi komunikasi digital melalui perencanaan konten yang terstruktur, penggunaan identitas visual yang konsisten, serta pemanfaatan fitur interaktif Instagram seperti reels, polling, question box, hashtag, dan call to action. Strategi content pillar seperti Highlight, QnA with Bang Ipen, Seputar Event, dan Riding The Wave mampu meningkatkan engagement audiens dan memperkuat karakter brand perusahaan. Penerapan strategi tersebut berkontribusi terhadap peningkatan jumlah pengikut, suka, komentar, dan tayangan pada akun Instagram @vecha.event. Penelitian ini menunjukkan bahwa media sosial Instagram memiliki peran penting dalam membangun komunikasi digital yang efektif untuk meningkatkan brand awareness pada industri event organizer. Kata Kunci: strategi komunikasi digital, media sosial, Instagram, brand awareness, event organizer.